النزول الجملي للقرآن الكريم بين توقيفيّة الاجتهاد وتوفيقيّته دراسة نقديّة: (The Wholesome Revelation (al-Nuzūl al-Jumalī) of the Qur’an between Suspensive and Accommodative Ijtihad: A Critical Study) - نجم أديولي شرف; سعيد عبد الله بوصيري (At-Tajdid - Intellectual Refereed Journal, 2022)
Among the information inherited from the sources of the sciences of the Noble Qur’an, from classical and modern Islamic literature is the issue of “Nuzūl al-Qur’ān” (the revelation of the Qur’an). The scholars of exegeses of the Qur’an have two main differing opinions: The first opined that Qur’an was revealed in batches with explicit evidence from the Qur’an and Sunnah while the second viewed that the Qur’an was revealed in wholesome with reference to Ibn Abbas as an authority of the Ummah, having elevated verdict to the prophets (PBUH), claiming that he does not say any verdict except that which he heard especially on tawqīfī (revelation-based) without the need for Ijtihad (intellectual diligence). Accordingly, scholars of tafsir accorded the second opinion the status tawqīfī (revelation-based) that prohibits jurisprudential opinions, while others considered it as a consensus opinion where Ijtihad is closed, although the narrated tradition from Ibn Abbas has the consideration between the tawqīfī (revelation-based) and tawfīqī (opinion-based) Ijtihad. So, it accommodates the possibility of other scholastic views and interpretations. Therefore, this study aims to examine the validity of the tawqīfī (revelation-based) specified by Allah in the Qur’an in respect of being revealed in wholeness and explication of the ambiguities surrounding it. In doing so, the study follows two basic approaches: The first is the inductive approach used in extrapolating the articles and publications written on the issue of total revelation and its consequences. The other is the analytical approach used in analyzing the opinions of scholars on the issue and criticizing it where necessary, then weighing the opinions as much as possible for juristic preference and trying to do the tarjīh between opinions as much as possible.. Keywords: Wholeness revelation, batch revelation, wholeness revelation-based & wholesness opinoin-based.